ENHANCING THE PROBLEM-SOLVING AND CRITICAL THINKING SKILLS OF STUDENTS USING THE MATHEMATICAL INVESTIGATION APPROACH - BUCU, ALJON (Studies in Technology and Education, 2022)
The interest in understanding what is involved in doing mathematical investigations brought together several researchers and classroom teachers. In this paper, the proponent decided to set up a project to experiment with tasks involving students exploring and investigating mathematical ideas, concepts, and processes. The work includes producing, experimenting, and evaluating such tasks and studying the competencies needed for using them successfully in the mathematics classroom. This study aimed to describe the attitude and performance of the students when exposed to investigative tasks. It is also driven to compare the performance of the control and experimental groups in relation to the implementation of the intervention and to see whether their attitude towards math investigation matters in the students' problem-solving and critical thinking skills. The findings showed that on the attitudes, the experimental group has a very favorable attitude toward the process of doing the investigation in spite of its complexity particularly in giving proof. The data obtained claimed that the control group did meet the expectations for both tests while the experimental post-test presented a very satisfactory performance indicating that their exposure to investigations taught them to explore and provide absolute mathematical reasoning. A significant difference was found in the performance of the two groups making the experimental group better than the control group as reaffirmed in the effect size of large. Further, students’ attitudes on the implementation of math investigation are described as a predictor of successful problem solving and improving the critical thinking skills of the students.